Global and Historical Distribution of Clostridioides difficile in the Human Diet (1981–2019): Systematic Review and Meta-Analysis of 21886 Samples Reveal Sources of Heterogeneity, High-Risk Foods, and Unexpected Higher Prevalence Toward the Tropic - Rodriguez-Palacios, Alexander; Mo, Kevin Q.; Shah, Bhavan U.; Msuya, Joan; Bijedic, Nina; Deshpande, Abhishek; Ilic, Sanja (Frontiers in Medicine, 2020)
Clostridioides difficile (CD) is a spore-forming bacterium that causes life-threatening intestinal infections in humans. Although formerly regarded as exclusively nosocomial, there is increasing genomic evidence that person-to-person transmission accounts for only <25% of cases, supporting the culture-based hypothesis that foods may be routine sources of CD-spore ingestion in humans. To synthesize the evidence on the risk of CD exposure via foods, we conducted a systematic review and meta-analysis of studies reporting the culture prevalence of CD in foods between January 1981 and November 2019. Meta-analyses, risk-ratio estimates, and meta-regression were used to estimate weighed-prevalence across studies and food types to identify laboratory and geographical sources of heterogeneity. In total, 21886 food samples were tested for CD between 1981 and 2019 (96.4%, n=21084, 2007-2019; 232 food-sample-sets; 79 studies; 25 countries). Culture methodology, sample size/type, region, and latitude were sources of heterogeneity (p<0.05). Although non-strictly-anaerobic methods were reported in some studies, and we confirmed experimentally that improper anaerobiosis of media/sample-handling affects CD recovery in agar (Fisher, p<0.01), most studies (>72%) employed the same (one-of-six) culture strategy. Because the prevalence was also meta-analytically similar across six culture strategies reported, all studies were integrated using three meta-analytical methods. At the study level (n=79), the four-decade global cumulative-prevalence of CD in the human diet was 4.1% (95%CI=-3.71, 11.91). At the food-set level (n=232), the weighted prevalence ranged between 4.5% (95%CI=3-6%; all studies) and 8% (95%CI=7-8%; only CD-positive-studies). Risk-ratio ranking and meta-regression showed that milk was the least likely source of CD, while seafood, leafy green vegetables, pork, and poultry carried higher risks (p<0.05). Across regions, the risk of CD in foods for foodborne exposure reproducibly decreased with Earth latitude (p<0.001). In conclusion, CD in the human diet is a global nonrandom-source of foodborne exposure that occurs independently of laboratory culture methods, across regions, and at variable level depending on food type and latitude. The latitudinal trend (high CD-food-prevalence towards tropic) is unexpectedly inverse to the epidemiological observations of CD-infections in humans (frequent in temperate regions). Findings suggest the plausible hypothesis that ecologically-richer microbiomes in the tropic might protect against intestinal CD colonization/infections despite CD ingestion.